PENGARUH KEMAHALAN KONSTRUKSI, KEMANDIRIAN FISKAL DAN PERTUMBUHAN EKONOMI TERHADAP PEMBANGUNAN MANUSIA DI SUMATERA BARAT - Hikmah J Rahmadhani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research aims to find out: (1) The Effect of Construction Overpriced on Human Development in West Sumatra. (2) Effect of Fiscal Independence on Human Development in West Sumatra. (3) Effect of Economic Growth on Human Development in West Sumatra. (4) The Effect of Construction Cost, Fiscal Independence, and Economic Growth Together on Human Development in West Sumatra. This type of research is descriptive and associative. Data type is secondary data. This study uses panel data, namely using 19 districts / cities in West Sumatra using the Fixed Effect Model (FEM) approach. The results of this study indicate that: (1) Construction Expenses have a negative and significant effect on Human Development in West Sumatra. (2) Fiscal Independence has a negative and insignificant effect on Human Development in West Sumatra. (3) Economic growth has a positive and significant effect on Human Development in West Sumatra.